An eco-friendly detoxification of chlorpyrifos by Bacillus cereus MCAS02 native isolate from agricultural soil, Namakkal, Tamil Nadu, India. (January 2018) - Duraisamy, Kavitha; Muthusamy, Sureshkumar; Balakrishnan, Senthilkumar
Abstract: Chlorpyrifos (CP) is one of organophosphorus (OP) compounds used as pesticides in the agriculture field in India. The persistence of CP causes environmental pollution and act as a nervous agent that affect human and animals health. Response surface methodology (RSM) was explored to optimize the biodegradation conditions of CP using Bacillus cereus MCAS 02 isolate from agriculture soil. The optimum biodegradation conditions were found to be pH 7.5, 90 rpm, 32 °C and 2.5 gL −1 . Under these conditions, B. cereus reached a maximum CP degradation (89%). Besides, a mathematical model was developed herein, and this model could be effectively used to predict and optimize the CP degradation conditions by B. cereus within the limits of chosen factors. In this optimum Mineral salt medium (MSM) with chlorpyrifos, B. cereus could breakdown the CP into 3, 5, 6-trichloro-2- pyridinol (TCP) and Diethyl Phosphorothioate (DETP), and its formation was confirmed by the m/z peak of GC– MS analysis, which was later metabolized to unknown polar metabolites. B. cereus has the ability to produce organophosphorus hydrolase (OPH) enzyme which is involved in the degradation of mentioned compounds. The results obtained highlights that the application of CP favored B. cereus harbors metabolic pathway for detoxification of CP and its hydrolysis product TCP into polar metabolites. Thus, it is suggested that B. cereus will be a potential agent and a boon for the bioremediation of CP contaminated agriculture soil field and associated water environment, thereby avert pollution and health hazards. Highlights: Bacillus cereus MCAS 02 mediated bioremediation of chlorpyrifos contaminated agriculture soil. Optimization of chlorpyrifos degradation by Box-Behnken design. Toxic intermediates resulting of chlorpyrifos degradation determined by GC-MS analysis.